The Econometric Models of the Analysis of the Development of Economic Processes - Мартишюс, Стасис (Ekonomika, 1995)
Econometric models Combines all statistic methods into a system. The econometric analysis of the economic indicators have to be complex and performed in stages. Forecasting the national economy’s processes, it is necessary to bear in mind the ageing of formation and the instability of its flow.